Hester se Brood - Van der Walt, Hester (Book collections on Project MUSE., 2009)
Hester se Brood, in Afrikaans, is set in a small town in the Little Karoo, where Hester van der Walt bakes bread in a woodfired oven for the local market in MacGregor. The book is inhabited by the spirit of the poets C. Louis Leipoldt and Martin Versfeld, as Hester van der Walt has the same deep rooted, intuitive connection between food and soul, especially food that is prepared with traditional ingredients and methods. Along with generous portions of soul food comes a down to earth delicious recipes that show you how to bake classic European breads, like ciabatta, focaccia, kitke and baguette.